Hubungan Self Efficacy dengan Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas IIIB SDN 10 Sapiran Bukittinggi - Reza Oktaviani; Iltavia; Aprismawati (Jurnal Pendidikan Dasar Islam, 2023)
The aim of this research is to see the relationship between self-efficacy and the mathematics learning outcomes of class III.B students at SDN 10 Sapiran Bukittinggi. This research uses quantitative methods with a correlational approach. The subjects of this research were class III.B students at SDN 10 Sapiran Bukittinggi, consisting of 11 students. The instruments used in this research were self-efficacy questionnaires and Mid-Semester Exam scores as learning outcomes. This research uses descriptive analysis and hypothesis test analysis. The product moment correlation test was used as an assumption test which ultimately resulted in the fact that there was no relationship or correlation between self-efficacy and Mid-Semester Exam scores for class III.B students at SDN 10 Sapiran Bukittinggi for the 2022/2023 academic year. The results of this research are shown by finding r= 0.126 and tcount (0.384) > ttable (1.833). However, even though no relationship was found between self-efficacy and student learning outcomes, it is hoped that students will continue to increase their self-efficacy in learning, especially in mathematics learning so that they are more confident and able to complete an activity well without any doubt or fear.